Aktualisasi Kurikulum Merdeka Berbasi PJBL dalam Mengembangkang Soft Skill Siswa di SDI Al Hadad Kedungjambe - Rosyidah, Irma; Badriyah, Yuni Nur; Aminuddin, Yusuf (Madrasah Ibtidaiyah Education Journal, 2024)
An independent curriculum continues the direction of previous curriculum development. This independent curriculum is based on project-based learning (PjBL). In this learning, students need their soft skills to optimally fulfill and complete the level of class activities. The focus of the problem in this research is the actualization of an independent curriculum based on Project Learning (PjBL) in developing students' soft skills at SDI Al Hadad Kedungjambe Singgahan Tuban. This research uses a qualitative descriptive approach with a case study type of research. This research uses observation methods, structured interviews, and documentation. The research results show that the actualization of the independent curriculum based on project-based learning (PjBL) in developing students' soft skills at SDI Al Hadad, namely the new independent curriculum, will be implemented in the 2022-2023 academic year and has only been implemented in classes I and IV. This independent curriculum contains the main pillars of educational policy guidelines, namely the Pancasila lesson profile, which consists of six dimensions, including a) faith, devotion to God Almighty, b) global diversity, c) cooperation, d) independence, e) critical reasoning, and f) creativity. The independent curriculum implements project-based learning (PjBL). This is to discover how independent and creative the students are in developing the soft skills they possess internally and externally. Supporting factors include: institutional readiness for implementing an independent curriculum based on project-based learning (PjBL), the active role of students, the creativity of students, and the creativity of teachers in learning that implements an independent curriculum based on project-based learning (PjBL). while the inhibiting factors are: Limited educators in teaching the independent curriculum, limited references at the institution, and time management arrangements.